A portable lab for the practical study of modern computer engineering - Dias, Tiago (2020)
This demo paper presents the μLIC educational platform. μLIC makes available to the students of Digital Systems and Computer Architecture courses a quite simple, intuitive and portable hardware platform for the realization of their laboratory exercises. μLI C can also be used in other related courses, such as Embedded Systems or Hardware/Software Co-Design, which allows reducing the time needed to study the manuals of diverse development boards and tools and to concentrate the education towards the core contents of the courses. In addition, the low cost, diminished size, and portable nature of the μLIC boards enables students to carry a personal unit with them all the time to implement the class exercises also outside the classrooms, as well as hobby projects. In the demo, three typical lab assignments of Digital Systems, Computer Architecture, and Hardware/Software Co-Design courses are used to showcase the μLIC educational platform: a traffic light controller, a 4-bit Arithmetic and Logic Unit (ALU) and a mini Space Invaders inspired game, respectively.